Comparative analysis of physical preparedness indicators among wrestlers of different qualifications - Tropin, Y.; Kovalenko, Y. (International Journal of Wrestling Science, 2023)
PURPOSE: This study aims to conduct physical fitness testing among wrestlers of different qualifications to identify differences in physical preparedness indicators.